Bilateral sinonasal polyposis in a patient with unilateral choanal atresia1. (10th September 2012) - Lee, Brian; Patel, Nimish; Ferguson, Berrylin J.
Abstract Sinonasal polyposis is a disorder of hyperplastic mucosal inflammation that subsequently leads to the development of smooth, pale, non‐neoplastic masses. The theories on its pathogenesis are diverse and remain debated within the medical community. A distinct, widely accepted, and unifying theory is absent, and probably unrealistic given the varying possible causes. The case reported here, which demonstrates nasal polyp formation within an atretic nasal cavity, suggests that nasal airflow or aerodynamics may have little to no effect on its etiology. It also seems to provide evidence that at least in some individuals nasal polyps appear to be due to an inflammatory disorder independent of inhalant allergen challenge. Laryngoscope, 2013